The formation of the high Tc phase of melt quenched Bi1.6Pb0.4Sr2Ca2Cu3Oy - Natividad, Michelle T. (Animo Repository, 2008)
The melt quench method was applied in the fabrication of Bi1.6Pb0.4Sr2Ca2Cu3Oy superconducting ceramics. The effects of melting the lead doped BSCCO were investigated using the scanning electron microscope and energy dispersive spectroscope (SEM/EDAX), differential thermal analyzer (DTA), x-ray diffractrometer (XRD) and magnetic susceptibility (χ-T) analyses. The results showed that the superconducting phase appeared even in the precursor samples. Glass forming tendency is also remarkably retarded. Sintering at 840°C for 24 hours completely vanished this glass forming ability. The critical temperature (Tc) onset was strongly dependent on the amount of non-superconducting impurities, grain size and intensity of the endothermic peak that affects the phase formation in the partially melted state.